Population variation in anti-S. aureus IgG isotypes influences surface protein A mediated immune subversion. Issue 15 (4th April 2016) - Whitehouse, Julia; Flaxman, Amy; Rollier, Christine; O'Shea, Matthew K.; Fallowfield, Joanne; Lindsay, Michael; Gunner, Frances; Knox, Kyle; Wyllie, David H.; Yamaguchi, Yuko
Highlights: There is marked variation in anti- S. aureus antibodies between healthy humans. Serum IgG1 against S. aureus surface antigens declines as adults age. High anti- S. aureus IgG3 levels bypass bacterial subversion of phagocyte function. Properties of IgG subclasses should be considered in S. aureus vaccine development. Abstract: Background: Staphylococcus aureus is a pathogen which causes life-threatening infection, the incidence of which rises during adult life. This, together with the emergence of drug-resistant strains and the expansion of more susceptible elderly populations, represents the rationale for the ongoing development of S. aureus vaccines targeting adult populations. Humoral responses to S. aureus naturally develop early in life, influence susceptibility to infection, and potentially influence the effect of vaccination. Despite this, the nature of pre-existing anti- S. aureus antibodies in healthy adult populations is not fully characterised. Methods: Immunoglobulin levels against S. aureus surface antigens were measured by a filter membrane enzyme-linked immunosorbent assay using fixed ΔSpA S. aureus as an antigen in serum samples obtained from three clinical cohorts comprising 133 healthy adult volunteers from 19 to 65 years of age. Functional capacity of antibody was also assessed, using antibody-mediated attachment of FITC-stained S. aureus to differentiated HL-60 cells. Results: Wide variation in the concentrations of immunoglobulins recognising S. aureus surface antigens was observed among individuals in all three cohorts. There was a decline of anti- S. aureus IgG1 with age, and a similar trend was observed in IgM, but not in IgA or other IgG sub-classes. Antibody mediated bacterial attachment to cells was associated with IgG1 and IgG3 concentrations in serum. The presence of SpA on the bacterial cell surface reduced antibody-mediated binding of bacteria to phagocytes in serum with low, but not high, levels of naturally occurring anti- S. aureus IgG3 antibodies. Conclusions: Naturally acquired immunoglobulin responses to S. aureus are heterogeneous in populations and their concentrations alter during adulthood. Elevated IgG1 or IgG3 titres against S. aureus enhance S. aureus recognition by phagocytosis and may be correlates of natural protection and/or vaccine efficacy in adult populations.